Effect of large doses of parenteral vitamin D on glycaemic control and calcium/phosphate metabolism in patients with stable type 2 diabetes mellitus: a randomised, placebo-controlled, prospective pilot study (Swiss Medical Weekly, 2014)
OBJECTIVE: Vitamin D (D3) status is reported to correlate negatively with insulin production and insulin sensitivity in patients with type 2 diabetes mellitus (T2DM). However, few placebo-controlled intervention data are available. We aimed to assess the effect of large doses of parenteral D3 on glycosylated haemoglobin (HbA1c) and estimates of insulin action (homeostasis model assessment insulin resistance: HOMA-IR) in patients with stable T2DM. MATERIALS AND METHODS: We performed a prospective, randomised, double-blind, placebo-controlled pilot study at a single university care setting in Switzerland. Fifty-five patients of both genders with T2DM of more than 10 years were enrolled and randomised to either 300,000 IU D3 or placebo, intramuscularly. The primary endpoint was the intergroup difference in HbA1c levels. Secondary endpoints were: changes in insulin sensitivity, albuminuria, calcium/phosphate metabolism, activity of the renin-aldosterone axis and changes in 24-hour ambulatory blood pressure values. RESULTS: After 6 months of D3 supply, there was a significant intergroup difference in the change in HbA1c levels (relative change [mean ± standard deviation] +2.9% ± 1.5% in the D3group vs +6.9% ± 2.1% the in placebo group, p = 0.041) as HOMA-IR decreased by 12.8% ± 5.6% in the D3group and increased by 10% ± 5.4% in the placebo group (intergroup difference, p = 0.032). Twenty-four-hour urinary albumin excretion decreased in the D3 group from 200 ± 41 to 126 ± 39, p = 0.021). There was no significant intergroup difference for the other secondary endpoints. CONCLUSIONS: D3 improved insulin sensitivity (based on HOMA-IR) and affected the course of HbA1c positively compared with placebo in patients with T2DM. Clinical trial registration number at ClinicalTrials.gov: NCT01585051